2000
DOI: 10.1016/s0896-6273(00)81205-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Rescaling Maximizes Information Transmission

Abstract: Adaptation is a widespread phenomenon in nervous systems, providing flexibility to function under varying external conditions. Here, we relate an adaptive property of a sensory system directly to its function as a carrier of information about input signals. We show that the input/output relation of a sensory system in a dynamic environment changes with the statistical properties of the environment. Specifically, when the dynamic range of inputs changes, the input/output relation rescales so as to match the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
611
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(641 citation statements)
references
References 20 publications
15
611
6
Order By: Relevance
“…In accordance with our findings it was shown in a recent study (Brenner et al 2000) that, in a certain dynamic range of motion stimulation, the peak response amplitude of a fly motion sensitive TC (the H1-cell) changes only relatively little when the standard deviation of white-noise velocity fluctuations is increased. This result was interpreted as a consequence of adaptive processes in the fly's motion pathway, which are assumed to rescale the input/output relation (Brenner et al 2000).…”
Section: Specificity Of Neuronal Responses Under Naturalistic and Simsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with our findings it was shown in a recent study (Brenner et al 2000) that, in a certain dynamic range of motion stimulation, the peak response amplitude of a fly motion sensitive TC (the H1-cell) changes only relatively little when the standard deviation of white-noise velocity fluctuations is increased. This result was interpreted as a consequence of adaptive processes in the fly's motion pathway, which are assumed to rescale the input/output relation (Brenner et al 2000).…”
Section: Specificity Of Neuronal Responses Under Naturalistic and Simsupporting
confidence: 93%
“…This condition is realized when the function relating the response amplitude to the input level is matched to the statistical distribution of stimulus levels. This kind of matched coding was concluded to operate in the peripheral visual system of the fly (for a review see Laughlin 1994) as well as at the level of TCs (Brenner et al 2000). In contrast to the conclusion obtained for a fly TC when stimulated with random velocity fluctuations, our results indicate that matched coding cannot be the reason for the peculiar performance of the HSE cell under naturalistic stimulus conditions.…”
Section: Functional Aspectscontrasting
confidence: 79%
See 1 more Smart Citation
“…Bialek and colleagues [61,62] have demonstrated that adaptation of the fly's H1 neuron to the variance of a white noise stimulus appears to optimize information trasmission.…”
Section: Extensionsmentioning
confidence: 99%
“…But if the neural response depends on more than a single axis within the stimulus space, the STA will provide an insu cient and possibly misleading description. A number of authors have suggested the natural extension of examining higher-order statistical properties (and in particular, the covariance) of the spike-triggered ensemble of stimuli [2,3,8,9,11]. The idea is simple and intuitive: if the neural response is deter-mined by a projection onto a low-dimensional subspace (within the space of all stimuli), an analysis of the spike-triggered covariance might allow us to recover this subspace.…”
Section: Recovery Of the Linear Subspace Using Spike-triggered Covarimentioning
confidence: 99%